The Transformation of a Unilateral Locomotor Command into a Symmetrical Bilateral Activation in the Brainstem - Brocard, Frédéric (J Neurosci, 2010)
A unilateral activation of the mesencephalic locomotor region (MLR) produces symmetrical bilateral locomotion in all vertebrate species tested to date. How this occurs remains unresolved. This study examined the possibility that the symmetry occurred at the level of the inputs from the MLR to reticulospinal (RS) cells. In lamprey semi-intact preparations, we recorded intracellular responses of pairs of large, homologous RS cells on both sides to stimulation of the MLR on one side. The synaptic responses on both sides were very similar in shape, amplitude, and threshold intensity. Increasing MLR stimulation intensity produced a symmetrical increase in the magnitude of the responses on both sides. Ca(2+) imaging confirmed the bilateral activation of smaller-sized RS cells as well. In a high-divalent cation solution, the synaptic responses of homologous RS cells persisted and exhibited a constant latency during high-frequency stimulation. Moreover, during gradual replacement of normal Ringer's solution with a Ca(2+)-free solution, the magnitude of responses showed a gradual reduction with a similar time course in the homologous RS cells. These results support the idea that the MLR projects monosynaptically to RS cells on both sides with symmetrical inputs. During locomotion of the semi-intact preparation, the discharge pattern was also very similar in homologous bilateral RS cells. Anatomical experiments confirmed the presence of MLR neurons projecting ipsilaterally to the reticular formation intermingled with neurons projecting contralaterally. We conclude that the bilaterally symmetrical MLR inputs to RS cells are likely contributors to generating symmetrical locomotor activity.